The church of solitude - Deledda, Grazia, 1871-1936 (SUNY series, women writers in translation., 2002)
"The Church of Solitude tells the story of Maria Concezione, a young Sardinian seamstress living with breast cancer at the cusp of the twentieth century. Overwhelmed by the shame of her diagnosis, she decides that no one can know what has happened to her, but the heavy burden of this secrecy changes her life in dramatic ways and almost causes the destruction of several people in her life. This surprising novel paints the portrait of a woman facing the unknown with courage, faith, and self-reliance, and is the last and most autobiographical work of Grazia Deledda, who died of breast cancer in 1936, shortly after its publication. An afterword by the translator offers additional information on the author and examines the social and historical environment of that time."--Jacket